Black Panther the ultimate guide - Wiacek, Stephen (New York DK Publishing, 2018)
A history of Marvel's iconic character, Black Panther. Wiacek discusses key themes and storylines, with character studies, historical insights, and a discussion on the philosophical importance in the 1960s of a comic book with an all-black cast of heroes and villains
Introduction -- Man of the moment -- Prince of heroes -- Man of mystery -- Defender of the faith -- Heavy sits the crown -- Out of Africa -- The most dangerous man alive -- The end of days -- Once and future king
At head of title: Marvel
Famous People
Includes index
Item is not a graphic novel
1
Keywords: Black Panther -- (Fictitious character) -- History; COMICS & GRAPHIC NOVELS / Media Tie-In; COMICS & GRAPHIC NOVELS / Superheroes; Superheroes -- History; Comics (Graphic works)